INNV-25. RITUXIMAB MONOTHERAPY FOR TREATMENT OF RARE LOW GRADE PRIMARY CENTRAL NERVOUS SYSTEM LYMPHOMA; A CASE REPORT AND LITERATURE REVIEW. (12th November 2021) - Tobin, Grace; Neil, Elizabeth
Abstract: Primary central nervous system lymphoma (PCNSL) is a specific variant of non-Hodgkin's lymphoma confined to the brain, leptomeninges, spinal cord, and/or eyes. The majority of PCNSL is diffuse large B-cell lymphoma (DLBCL), however, a small percentage are categorized as low-grade lymphomas (LGL). Compared to high-grade and aggressive DLBCL, LGL are indolent; allowing for targeted and less neurotoxic first-line treatments. There is currently no consensus for LGL treatment. A patient at our institution was diagnosed with LGL without extra-CNS involvement 11/2018 and then, successfully treated with rituximab monotherapy. This 65 year-old, immunocompetent woman presented with one month of right leg weakness and numbness. Brain MRI demonstrated a subtly enhancing infiltrative left thalamic lesion extending into the left frontal lobe with surrounding edema. Flow cytometry on spinal fluid showed rare monotypic B-cells. Brain biopsy results showed an atypical predominantly perivascular lymphoid infiltrate. These atypical small lymphoid cells had mature-appearing nuclear chromatin, absent nucleoli, and uniformly expressed CD79a and CD20 with variable PAX-5 expression, lacked CD56 and CD117 expression, and had plasmacytic differentiation; thus consistent with marginal zone lymphoma, a type of indolent B-cell lymphoma. There was no evidence of extra-CNS involvement on PET scan, bone marrow biopsy, or ocular exam. She had normal cognitive functioning on neuropsychological testing. Interestingly, SPEP showed a monoclonal IgM immunoglobulin of kappa-light chain-type that became a monoclonal protein in the gamma fraction. Additionally, CT abdomen initially showed splenomegaly that resolved on repeat imaging a year later. Radiation therapy was deferred due to high risk. Weekly rituximab 500mg/m2 was initiated for 4 doses, then monthly for 4 doses. Therapy was well tolerated and she noted clinical improvement plus there was positive response on brain imaging. Repeat ophthalmology exam and CT body without any evidence of cancer. She is now 29 months progression-free since completing rituximab.